Seasonal variation in prevalence, parasite load and mean intensity of ectoparasites in Pipistrellus kuhlii (Chiroptera: Vespertilionidae) from Iran - Sharifi, Mozafar; Vaissi, Somaye; Javanbakht, Hossein (Acta Biologica Szegediensis, 2019)
We studied quantitatively the seasonal variation in prevalence, parasite load, and mean intensity of two species of ectoparasites in free ranging populations of Kuhl's bat, Pipistrellus kuhlii in western Iran. In total, 348 live bats (230 males and 118 females) were collected using mist net during May to November 2013. All bats identified as to sex and the number of ectoparasite species in each bat was counted. On 348 P. kuhlii captured, 5355 ectoparasites were observed. Two species of ectoparasites belonging to Argas vespertilionis (Argasidae) and Steatonyssus sp. (Macronyssidae) were identified. In late May and at the beginning of June, the peaks of ectoparasite load in bats were recorded and then dropped during June to November. The number of ectoparasites in pregnant female bats in May-June during pregnancy was significantly higher than non-pregnant females (p ≤ 0.05). A significant correlation was found between ectoparasite load and the ratio of body mass to the length of forearm (W/FA), as an index of body condition, indicating that parasite load has apparent impact on bat’s health. Our findings indicated that parasite loads correlate with season, sex and reproductive condition of the host.